Research on Dynamic Venting Characteristics of City Gas Pipeline Networks and Analysis of Software Development - Weng, Yu; Sun, Xiaomao; Gou, Mengjiao; Liu, Bohua; Yang, Shuang; Deng, Zhian (Transactions on Computer Science and Intelligent Systems Research, 2023)
As an important part of the gas pipeline safety system, the venting pipe plays a role in protecting the safe operation of the network and reducing the consequences of accidents, and its design feasibility, rationality and safety are particularly important. In China, most of the online simulation software used for gas pipeline network venting simulation is limited to expensive, poorly controllable software and difficult to design for specific working conditions, so the application of dynamic simulation software for gas pipeline networks is of great importance. In this paper, simulation software is developed for city gas pipeline venting systems, simulations are carried out using a programming language, the usability of the developed software is verified and the influence of different influencing factors on the venting process is investigated using the control variable method of analysis.